The Role of the Financial Services Authority in Handling Online Money Loan Offers by Information Technology-Based Joint Funding Services (LPBBTI) - Aurelia Natalia Wisung; Sukardan Aloysius; Yossie M.Y. Jacob; Darius Mauritsius (Catuspata, 2023)
The Financial Services Authority is a financial services supervisory institution that has the authority to regulate, supervise, examine, and investigate financial services institutions including online money loans by information technology-based joint funding services. The formulation of this research problem: (1) What is the role of the Financial Services Authority in handling online money loan offers by information technology- based joint funding services? (2) what efforts have the Financial Services Authority made in handling online money loan offers by information technology-based joint funding services? The research used is normative legal research using the descriptive analysis method. This research uses primary, secondary, and tertiary legal materials. The results of this study can be concluded: (1) The role of the Financial Services Authority in handling online money loan offers by information technology-based joint funding services is to issue regulations to regulate and supervise. (2) The efforts that have been made by the Financial Services Authority in handling online money loan offers by information technology-based joint funding services are conducting education, urging the public to always check the legality of online loans when receiving offers, issuing new services to improve consumer protection, namely Consumer Support Technology (CST) in the form of Chatbot CST and the Financial Services Authority together with 11 ministries coordinating to form the Investment Alert Task Force (SWI) to eradicate illegal online loans that are troubling and detrimental to the community.